2019
DOI: 10.1111/jmft.12420
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Adolescent Abuse on Relationship Quality and Posttraumatic Stress Symptoms in Mother–Adolescent Dyads

Abstract: The current study examined dyadic reports of mother-adolescent relationship quality (RQ) as a mechanism by which emotional, physical, and sexual abuse affect posttraumatic stress symptoms (PTSS) over time from a family systems perspective. We used three waves of data from the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN), including 321 mother-adolescent dyads observed when adolescents were approximately 12, 14, and 16 years old. We used an extended version of the actor-partner interdependence medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Consistent with prior research, we found that maternal–adolescent relationship quality, and adolescent perceptions specifically, is an important factor in understanding adolescent mental health (Fitzgerald & Ledermann, 2020). Prior research has noted that the parent–adolescent relationship, characterized by communication, closeness, trust, alienation, and conflict, play an integral role in understanding adolescent mental health (Branje et al, 2010; Bynum & Kotchick, 2006; Ebbert et al, 2018; Fanti et al, 2008; Marganska et al, 2013; McWey et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with prior research, we found that maternal–adolescent relationship quality, and adolescent perceptions specifically, is an important factor in understanding adolescent mental health (Fitzgerald & Ledermann, 2020). Prior research has noted that the parent–adolescent relationship, characterized by communication, closeness, trust, alienation, and conflict, play an integral role in understanding adolescent mental health (Branje et al, 2010; Bynum & Kotchick, 2006; Ebbert et al, 2018; Fanti et al, 2008; Marganska et al, 2013; McWey et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…One methodological reason that maternal relationship quality may not be associated with adolescent mental health is that adolescents reported on their own mental health. Prior studies using the LONGSCAN have found that maternal perceptions of relationship quality, but not adolescent reports, predicted maternal reports of adolescent mental health (McWey et al, 2015), whereas adolescent reports of relationship quality, but not maternal reports of relationship quality were significant when adolescents self‐reported their own mental health (Fitzgerald & Ledermann, 2020). Thus, within person reports of relationship quality and adolescent mental health are significant (e.g., adolescent report on both) and between person reports are non‐significant (e.g., maternal reports on relationship quality and adolescent report on own mental health).…”
Section: Discussionmentioning
confidence: 97%